Verospiron effects on platelet aggregation in patients with arterial hypertension and abdominal obesity - I. N. Medvedev; T. Yu. Nosova (Российский кардиологический журнал, 2007)
The study compared hypothiazide and verospiron effects on platelet aggregation inpatients with arterial hypertension (AH) and abdominal obesity (АО). The first group (n=28) received hypothiazide for 16 weeks, the second group (n=23) was administered verospiron for the same period. Dynamics of lipid profile, plasma and platelet lipid peroxidation products, blood and platelet antioxidant potential, as well as platelet aggregation activity, were assessed. The data were analysed using Student t test. Inpatients with AH and АО, verospiron therapy had beneficial effects on peroxidation syndrome and platelet aggregation. Long-term verospiron therapy could provide more sustainable effects. Hypothiazide did not affect the parameters assessed. To reduce body weight in patients with AH and АО, verospiron therapy should be combined with non-pharmaceutical methods.